2015
DOI: 10.1001/jamaneurol.2014.3780
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Immunosuppressive Therapy and Autologous Hematopoietic Cell Transplantation for Relapsing-Remitting Multiple Sclerosis (HALT-MS)

Abstract: IMPORTANCE Most patients with relapsing-remitting (RR) multiple sclerosis (MS) who receive approved disease-modifying therapies experience breakthrough disease and accumulate neurologic disability. High-dose immunosuppressive therapy (HDIT) with autologous hematopoietic cell transplant (HCT) may, in contrast, induce sustained remissions in early MS.OBJECTIVE To evaluate the safety, efficacy, and durability of MS disease stabilization through 3 years after HDIT/HCT. DESIGN, SETTING, AND PARTICIPANTS Hematopoiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
152
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(168 citation statements)
references
References 31 publications
11
152
1
4
Order By: Relevance
“…One study has looked at the efficacy of AHCT in patients with RRMS who have continued to have relapses while treated with disease-modifying therapies, including natalizumab [23]. This study showed that at 3 years, the event-free survival in patients treated with AHCT was 78.4%, which is higher than that reported in the AFFIRM study for natalizumab.…”
Section: Natalizumabmentioning
confidence: 91%
See 1 more Smart Citation
“…One study has looked at the efficacy of AHCT in patients with RRMS who have continued to have relapses while treated with disease-modifying therapies, including natalizumab [23]. This study showed that at 3 years, the event-free survival in patients treated with AHCT was 78.4%, which is higher than that reported in the AFFIRM study for natalizumab.…”
Section: Natalizumabmentioning
confidence: 91%
“…AHCT does lead to the suppression of production of certain types of T-cell [22,23], but the balance between regulatory and pro-inflammatory lymphocytes is re-set in favor of regulatory cells [24].…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Over the last decade, multiple efforts have been made to optimize the cell source, patient selection, and the safety and tolerability of stem cell-based therapies [74]. In a recent phase II trial, high-dose immunosuppressive therapy and autologous hematopoietic cell transplantation without maintenance therapy was found to be effective for inducing sustained remission of active RRMS at 3 years [78]. While autologous hematopoietic stem cell transplantation is based on utilizing hematopoietic cells to repopulate the immune system following high-dose immunosuppression, infusion of mesenchymal cells or autologous unfractionated bone marrow is not preceded by immunosuppression.…”
Section: Hematopoetic Stem Cell Therapymentioning
confidence: 99%
“…Summarizing the cited protocols, with domination of BEAM and Cy (200 mg/kg), both ±ATG/ alemtuzumab make an impression that in case of MS, lower intensity protocols demonstrate lower, up to 0%, mortality rate, while OS and progression-free survival are similar; in resent studies, they range from 65 to 100%, far better than the results of conventional MS therapies [77][78][79][80][81]. Our limited experience demonstrates 71% of progression-free survival after nonmyeloablative transplantations performed in Hadassah-HUJI Medical Center (14 patients, 1998-2016, 12 after autologous and 2 after allogeneic transplantation; S. Savin, R. Or, M. Shapira and I. Resnick; unpublished data).…”
Section: Hct For Multiple Sclerosismentioning
confidence: 99%